Two independent approaches to assessing the constancy of evaporative water loss for birds under varying evaporative conditions - Gilson, Lauren Noelle; Cooper, Christine; Withers, Philip Carew; Gagnon, Monique (Elsevier, 2021)
We examine here the effects on evaporative water loss (EWL), at and below thermoneutrality, of perturbing the evaporative environment for the red-capped parrot (Purpureicephalus spurius) by modifying the ambient relative humidity or the diffusive properties of the ambient environment using a helium-oxygen mix (helox). We found that evaporative water loss did not change with relative humidity at an ambient temperature of 30°C, but there was a negative relationship for evaporative water loss with relative humidity at 20 and 25°C. The EWL per water vapour pressure deficit between the bird and its ambient environment was not constant with relative humidity, as would be expected for a physical effect (slope = 0); rather there was a significant positive relationship with relative humidity at ambient temperatures of 25 and 30°C. Consequently, we conclude that the red-capped parrot can physiologically control its EWL over a range of relative humidities. For the first time for a bird species, we also confirmed EWL control using a second methodology to perturb the evaporative environment, and demonstrated that a more diffusive helox atmosphere has no effect on EWL of live birds, but EWL was higher for dead birds in helox compared to air. Our results for EWL and other physiological variables for red-capped parrots are consistent with the hypothesis that EWL is under physiological control.